Next time I'll aim for the heart [videorecording (DVD)] - Anger, Cédric; Anger, Cédric; Canet, Guillaume; Girardot, Ana, 1988-; Berteloot, Jean-Yves, 1958- (Icarus Films Home Video, 2018)
A police officer is tasked with solving a series of murders that he committed.